The effect of body weight-supported Tai Chi Yunshou on upper limb motor function in stroke survivors based on neurobiomechanical analysis: a four-arm, parallel-group, assessors-blind randomized controlled trial protocol - Zhang, Liying; Wang, Jiening; Zhou, Huanxia; Liao, Wangsheng; Wang, Naizhen; Yu, Xiaoming (Frontiers in Neurology, 2024)
Introduction: A series of functional disorders commonly occur after stroke, of which upper limb dysfunction is the most difficult to recover. The upper limb rehabilitation effect of Tai Chi Yunshou(TCY) in the later stage of stroke has been confirmed by research. Body weight support-Tai Chi Yunshou (BWS-TCY) is based on TCY exercise and robotic exoskeletons offers most flexibility in deweighting and control strategy. This study is aimed to explore the effect of BWS-TCY on upper limb motor function in stroke based on neurobiomechanics. Methods and analysis: A single-blind randomized controlled trial will be conducted on 36 stroke survivors who will be randomly assigned to three groups: experimental group, control group A and control group B. In addition, 12 healthy elderly people will be recruited into the healthy control group. Those in the experimental group will receive 20 minutes of CRT and 20 minutes of BWS-TCY training, while participants in the control group A will receive 20 minutes of CRT and 20 minutes of Robot-assisted training. Participants in the control group B will undergo 40 minutes of Conventional rehabilitation training (CRT) daily. All interventions will take place 5 days a week for 12 weeks, with a 12-week follow-up period. No intervention will be carried out for the healthy control group. Upper limb function will be assessed before and after the intervention using various rating scales (Fugl-Meyer Assessment, Wolf Motor Function Test, etc.), as well as neurobiomechanical analyses (surface electromyography, functional near-infrared brain function analysis system, and Xsens maneuver Capture System). Additionally, ten healthy elderly individuals will be recruited for neurobiomechanical analysis, and the results will be compared with those of stroke survivors. Discussion：The results of this study will offer initial evidence on the effectiveness and feasibility of BWS-TCY as an early intervention for stroke rehabilitation. Positive findings from this study could contribute to the development of guidelines for the use of BWS-TCY in the early stages of stroke. Trial registration number: Chinese Clinical Trials Registry (ChiCTR 2200063150)